Paradoxical Radiosensitizing Effect of Carnosic Acid on B16F10 Metastatic Melanoma Cells: A New Treatment Strategy - Miguel Alcaraz; Amparo Olivares; Marina Andreu-Gálvez; Daniel Gyingiri Achel; Ana María Mercado; Miguel Alcaraz-Saura (Antioxidants, 2022)
Carnosic acid (CA) is a phenolic diterpene characterized by its high antioxidant activity; it is used in industrial, cosmetic, and nutritional applications. We evaluated the radioprotective capacity of CA on cells directly exposed to X-rays and non-irradiated cells that received signals from X-ray treated cells (radiation induced bystander effect, RIBE). The genoprotective capacity was studied by in vivo and in vitro micronucleus assays. Radioprotective capacity was evaluated by clonogenic cell survival, MTT, apoptosis and intracellular glutathione assays comparing radiosensitive cells (human prostate epithelium, PNT2) with radioresistant cells (murine metastatic melanoma, B16F10). CA was found to exhibit a genoprotective capacity in cells exposed to radiation (p < 0.001) and in RIBE (p < 0.01). In PNT2 cells, considered as normal cells in our study, CA achieved 97% cell survival after exposure to 20 Gy of X-rays, eliminating 67% of radiation-induced cell death (p < 0.001), decreasing apoptosis (p < 0.001), and increasing the GSH/GSSH ratio (p < 0.01). However, the administration of CA to B16F10 cells decreased cell survival by 32%, increased cell death by 200% (p < 0.001) compared to irradiated cells, and increased cell death by 100% (p < 0.001) in RIBE bystander cells (p < 0.01). Furthermore, it increased apoptosis (p < 0.001) and decreased the GSH/GSSG ratio (p < 0.01), expressing a paradoxical radiosensitizing effect in these cells. Knowing the potential mechanisms of action of substances such as CA could help to create new applications that would protect healthy cells and exclusively damage neoplastic cells, thus presenting a new desirable strategy for cancer patients in need of radiotherapy.